Повышение надежности контакта тонкопленочных резисторов - Lugin, A. N.; Ozemsha, M. M. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
Necessity of resistive layer growth under the contact and in the contact zone of resistive element is shown in order to reduce peak values of current flow and power dissipation in the contact of thin film resistor, thereby to increase the resistor stability to parametric and catastrophic failures.